2012
DOI: 10.1248/bpb.b12-00037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macelignan Isolated from <i>Myristica fragrans</i> (Nutmeg) on Expression of Matrix Metalloproteinase-1 and Type I Procollagen in UVB-Irradiated Human Skin Fibroblasts

Abstract: Exposure to ultraviolet (UV) light causes premature skin aging that is associated with upregulated matrix metalloproteinases (MMPs) and decreased collagen synthesis. Macelignan, a natural lignan compound isolated from Myristica fragrans HOUTT. (nutmeg), has been reported to possess antioxidant and antiinflammatory activities. This study assessed the effects of macelignan on photoaging and investigated its mechanisms of action in UV-irradiated human skin fibroblasts (Hs68) by reverse transcription-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The use of macelignan as an antiphotoaging agent stems from its antioxidant, antionflammtory, as well as its documented ability to protect human skin fibroblasts against damaging effects of UVB irradiation. The observed protective effect is mediated by suppression of two cellular responses involved in premature skin aging: the upregulation of matrix metalloproteinases (MMPs) and reduced collagen synthesis (Lee et al 2012). Another potential skin application for macelignan was reported by Choi et al whereby the authors suggested the use of macelignan as a natural depigmenting agent based on its ability, at 10 M concentration, to inhibit melanosome transfer and dendrite formation in B16F10 melanoma cells (Choi et al 2011).…”
Section: Pharmacological Evaluation Of Pure Nutmeg Compoundsmentioning
confidence: 99%
“…The use of macelignan as an antiphotoaging agent stems from its antioxidant, antionflammtory, as well as its documented ability to protect human skin fibroblasts against damaging effects of UVB irradiation. The observed protective effect is mediated by suppression of two cellular responses involved in premature skin aging: the upregulation of matrix metalloproteinases (MMPs) and reduced collagen synthesis (Lee et al 2012). Another potential skin application for macelignan was reported by Choi et al whereby the authors suggested the use of macelignan as a natural depigmenting agent based on its ability, at 10 M concentration, to inhibit melanosome transfer and dendrite formation in B16F10 melanoma cells (Choi et al 2011).…”
Section: Pharmacological Evaluation Of Pure Nutmeg Compoundsmentioning
confidence: 99%
“…Previous studies have demonstrated the positive effects of herbal extracts in preventing skin photoaging: Sun et al (21) revealed that wild chrysanthemum extract downregulates ROS levels within HaCat cells and so reduces MMP-2 and MMP-9 expression by inhibiting UV-induced ERK1/2 and p38 phosphorylation to prevent UVB-related acute skin damage and photoaging. Lee et al (22) demonstrated that macelignan, an effective antioxidant found in the nutmeg, Myristica fragans , downregulates MMP-1 expression by reducing UV exposure-related ROS elevation and MAPK phosphorylation. In addition, it increases type I collagen expression by activating transforming growth factor β (TGF-β)/SMAD signaling to effectively prevent and treat skin photoaging.…”
Section: Introductionmentioning
confidence: 99%
“…UV irradiation induced protein expression of the AP-1 family members, c-Jun and c-Fos (Quan et al, 2005). Type I procollagen and elastin are elastic proteins that participate in organizational flexibility and elasticity (Lee et al, 2012;Zheng et al, 2012;Fan et al, 2013;Hwang et al, 2011;Devy et al, 2010). Transforming growth factor beta (TGF-β) is a protein that is involved with identity, function, and survival in cells.…”
Section: Introductionmentioning
confidence: 99%